KONSEP HAK ASASI MANUSIA DALAM ISLAM (Mengungkap Korelasi Antara Islam Dengan HAM) - Zein, Yahya Ahmad (Faculty of Law, Parahyangan Chatolic University, 2015)
Abstract The intention of this article is explore how Islamic teaching regards human rights. The main finding of this basic research is that in todays modern world, the universal values of human rights function as a glue binding society together. Although in pluralist modern society it become very difficult to impose one standard paradigm or worldview. In regard to Islam and human rights important is to take cognizance of the huquuqul ibad category. This enables us to differentiate between, firstly, the existence of human rights within a country and directly applicable and, secondly, human rights whose existence cannot be directly implemented by a country. Another finding is that there Islamic teaching does not contradict the universal value of human rights. There is a common ground (common values/kalimatun Sawa) between Shariah and human rights in which both demands the development of human virtues (rahmatal lilalamin/ nurturing the whole universe)Â Keywords: Concepts, human rights, Islam